PENDESTARIAN KEUNIKAN TARI NGEBENG WARISAN BUDAYA DI DESA RAMBUTAN MASAM KABUPATEN BATANGHARI - Mayang Ismaya; Raihan Noer Silmi; Suci Ramahdani; Feronika Meyora Sibagariang; Faras Rahayu; Winda Ismayanti; Dinda Risky Diwanti; Novi Aprilia Nazarmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research generally discusses the Ngebeng dance, which is one of the dances that lives and develops in Rambutan Masam Village and has become a characteristic of the community. The method used in this research is qualitative research which is research with the aim of understanding the phenomena experienced by the subject. This research procedure produces descriptive data in the form of written or spoken words from people and observable behavior. In this case, the researcher has conducted a survey first to obtain information in advance to obtain sources of information about the object through interviews, photos and videos. As for a brief description of the results of this research, the author analyzes the existence of the Ngebeng dance procession, referring to the function of dance which is categorized as a means of performance and entertainment for the people of Rambutan Masam Village and provides views on the Ngebeng dance which is interpreted as entertainment when tired in the rice fields and fields, as well as being performances at cultural events. On the other hand, the Ngebeng dance has become a medium of communication as a unifier and a proud cultural heritage for the local community. The Ngebeng dance is used to welcome distinguished guests who come to the village, to welcome days that are considered important, as entertainment events and as a place for friendship.